Kursbuch Geschichte der europäischen und globalen Moderne Arbeitsformen, Fragestellungen, Texttypen - Kunze, Rolf-Ulrich (KIT Scientific Publishing, 2022)
"Kursbuch Geschichte der europäischen und globalen Moderne" offers a compendium and study book on types of events, central terms and learning strategies in modern and contemporary European and global history as an exemplary history of technical-industrial modernity. Target groups are students of history, the humanities and social sciences as well as all technical and scientific subjects with an interest in modern history.